2011
DOI: 10.1007/s10008-011-1514-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of rare-earth doped LiMn2O4 spinel cathode materials for Li-ion rechargeable battery

Abstract: Spinel powders of LiMn 2−x RE x O 4 (RE = La, Ce, Nd, Sm; 0≤x≤0.1) have been synthesized by solid-phase reaction. The structure and electrochemical properties of these electrode materials were characterized by X-ray diffraction (XRD), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and charge-discharge experiment. The part substitution of rare-earth element RE for Mn in LiMn 2 O 4 decreases the lattice parameter, resulting in the improvement of structural stability, and decreases the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 29 publications
(32 reference statements)
2
27
0
Order By: Relevance
“…For instance, the nonmetals B [10][11][12], F [13][14][15], S [16], Br [17], the general metals Mg [18], Al [19], Ti [20,21], Cr [22,23], Fe [24], Co [19,[25][26][27], Ni [28], Cu [29], Zn [30][31][32], Ga [33], Zr [34], Ru [35], Ag [36,37], Sn [38], Au [39], the rare-earth metals La [40], Ce [41], Pr [42], Nd [43], Sm [44], Gd [45], and the actinide dopants Th [46], U [47]. Some researchers have also modified LiMn 2 O 4 with surface coating [48][49][50][51][52] electrolyte modification [53], laser annealing [54], pulsed laser deposition [55], process optimization …”
Section: Open Accessmentioning
confidence: 99%
“…For instance, the nonmetals B [10][11][12], F [13][14][15], S [16], Br [17], the general metals Mg [18], Al [19], Ti [20,21], Cr [22,23], Fe [24], Co [19,[25][26][27], Ni [28], Cu [29], Zn [30][31][32], Ga [33], Zr [34], Ru [35], Ag [36,37], Sn [38], Au [39], the rare-earth metals La [40], Ce [41], Pr [42], Nd [43], Sm [44], Gd [45], and the actinide dopants Th [46], U [47]. Some researchers have also modified LiMn 2 O 4 with surface coating [48][49][50][51][52] electrolyte modification [53], laser annealing [54], pulsed laser deposition [55], process optimization …”
Section: Open Accessmentioning
confidence: 99%
“…Cation doping is another effective way to modify the intrinsic properties of electrode materials for lithium-ion batteries. Previous studies have reported that the doping of metal ions into bulk materials can form more stable phase and increase the ionic or electrical conductivity, resulting in the improvement of cycling performance and rate capability [26][27][28][29][30]. It will favor fast charging and discharging if proper cation could be doped in LiVOPO 4 to improve its electrical conductivity or stable its crystal structure.…”
Section: Introductionmentioning
confidence: 97%
“…The capacity fading of pristine LiMn 2 O 4 is strongly inuenced from JahnTeller distortion occurring on the surface of the particles and manganese dissolution into the electrolyte, especially at elevated temperatures. To overcome these drawbacks, two strategies were mainly pursued: elements substitution or oxygen excess to increase the oxidation state of Mn for suppressing the Jahn-Teller eect and surface modication or coating for suppressing the dissolution of Mn into the electrolyte [3]. The rst strategy of doping is known to be an eective route.…”
Section: Introductionmentioning
confidence: 99%